Ensaio em transformadores de potência com regeneração utilizando carga eletrônica ativa em conexão série - Galvao, Thiago Moura (2019)
A setup for testing transformers, either rated values or slightly above, but low power consumption from grid, is presented in this work. Control of active and reactive power is performed by adding in series with the transformer to be tested a controlled voltage source. This is implemented by employing a 6-pulse DC-AC converter bridge with SPWM modulation (Sinusoidal Pulse Width Modulation). By controlling the direct and quadrature axis currents ( - ) through PI regulators, it is indirectly possible to control the active and reactive powers that circulate through the tested transformer, based on classical power flow studies between two system bus. It is also possible to inject harmonic currents into the tested transformer for recreating nonlinear conditions. As a result, the goal is achieved by employing a converter whose rated power is only a fraction of the rated power of the transformer under test (TUT). In addition, the consumed power of the grid is a fraction compared to the nominal of the test. The system’s analysis for transformer test with idq current control produces simulation results for several conditions of power factor, harmonics and power level, that proves expected working of the structure.